Response of plates subjected to air-blast and buried explosions - Curry, Richard (Blast Impact and Survivability Research Unit, 2018)
Explosive threats have become more prevalent in both military and terrorist theatres of conflict, showing up largely in the form of Improvised Explosive Devices (IED) which are often buried in soil to conceal them and increase their effectiveness. The response of a structure subjected to a blast load is influenced by many factors, namely stand off distance, mass of explosive, degrees of confinement and medium surrounding the charge. This study focuses on characterizing the transient deformation of test plates which have been exposed to different explosive loading conditions including free air blasts (AIR), backed charge (VBP) and buried charge (SBP) configurations. In the three loading configurations, four charge masses are considered, utilizing 10g, 15g, 20g and 25g masses of PE4 plastic explosive which were moulded into cylindrical charges of a constant 38mm diameter. The transient deformation of the test plates was captured using high speed Digital Image Correlation (DIC), which utilized two high speed cameras to record the experiments. Extensive modifications to the blast pendulum to incorporate the cameras was necessary to adapt this technique in a different method to that used in previous literature. The mounting method proposed allowed the cameras to record the experiment while capturing the impulse imparted on a test plate using a blast pendulum. The experimental plates exhibited only Mode I failure, which is plastic deformation, enabling the effect of different loading configurations on the transient and final plate deformation profiles to be identified. Numerical simulations of the experiments were developed to further the understanding of the load arising from the three configurations and the deformation mechanisms involved. The experimental results are used to validate the numerical models, which allow for a better understanding of the evolution of the deformation and strains across the plate. The transient data for the numerical simulation and the experiments were found to match closely. This work clearly shows the effect that the different loading conditions have on the tests plates, specifically the impulse distributions and transient strain in the plates. It was observed in this study that the impulse imparted on a test plate increases with the addition of sand while keeping other test conditions constant. The impulse recorded was observed to increase by 490-540% and 19-100% when compared to AIR and VBP 50mm SOD tests respectively. The loading profile acting on the test plate as a result of the specific impulse changes significantly with the inclusion of sand. The midpoint deflection increases with a decrease in stand off distance, increase in charge mass, increase in level of confinement or the inclusion of an overburden of sand. The observed increase in midpoint deflection of between 90-160% and 30-40% when compared to AIR and VBP 50mm SOD tests respectively was reported. The transient plate profile does not match the final deformation profile.